ISOLATION AND MOLECULAR DETECTION OF CLOSTRIDIUM CHAUVOEI ALPHA TOXIN GENE FROM CLINICAL CASES OF BLACK QUARTER IN CATTLE - A. Idrees; Z. I. Chaudhary; M. Younus; K. Ashraf (Journal of Animal and Plant Sciences, 2014)
The objective of the present study was to isolate and identify Clostridium chauvoei from swab (n=750) and tissue (n=50) samples from cattle suspected for black quarter in six districts belonging to different climatic zones (Punjab, Pakistan). Conventional culture methods showed 192(25.6%) and 19(38%) positive from swab and tissues respectively for this bacterium. These bacterial isolates were further processed and confirmed by Polymerase chain reaction (PCR) by amplifying and (Ccta) gene sequences. An amplicon of 836 bp corresponding to 16SrRNA genesequence was obtained. PCR confirmed 140 (72.9%) and 41 (82%) positive samples from swab and tissues respectively.It is concluded that PCR was found an efficient tool for precise detection of Clostridium chauvoei
Keywords: Black quarter; Clostridium chauvoei; cattle; PCR